A conscientização da comunicação não verbal na educação universitária - Brandão, Sonia Maria Miranda (1979)
This is an experimental work for testing the possibility of improving the training of non-verbal Communication, through a special Interactive course on the subjetc. The experimental research ~s preced by a theoretical approach showing the social importance of nonverbal Communication and how relevant it ~s Education, to lay stress on this area. for general At the part of this dissertation suggestions are apresented for the aplication of the research on the matter, based on this first ones.